Ozone exposure effect on systemic prostaglandin F2α in rat plasma and urine may not reveal pulmonary damage through inflammation. (November 2017) - Basu, Samar; Kadiiska, Maria B.
Abstract: The acute ozone induced lung injury model has been widely used to explore injury and repair processes induced by oxidant overload. The current study evaluated acute ozone exposure effects on prostaglandin F2α (PGF2α ) in male Fischer rat plasma and urine with the hypothesis that ozone may induce an inflammatory response in the body that can be measured by the induction of PGF2α . That might then lead to the identification of potential marker for acute lung injury through systemic inflammation. The time and dose-dependent effects of ozone exposure on the plasma and urinary levels of a major PGF2α metabolite15-keto-dihydro-PGF2α were determined using a radioimmunoassay. No statistically significant differences in the PGF2α metabolite were found between the control and the experimental groups at either ozone exposure dose (2 ppm and 5 ppm) or any time point (2 h, 7 h and 16 h) post exposure for plasma and at 7 different post exposure time points (between 2 and 80 h) for urine. It is concluded that acute ozone exposure does not cause changes in plasma and urinary PGF2α, and therefore their measurement in plasma and urine may not be used to reveal pulmonary inflammation and damage by ozone. Highlights: Ozone is a highly reactive molecule that can induce acute lung injury through oxidative stress and inflammation. Recognizing cellular participation we hence examined time and dose-dependent ozone exposure effects on inflammatory response in the rats and that can be measured by the induction of cyclooxygenase-mediated PGF2α. No statistically significant differences in the systemic PGF2 a metabolite were found between the control and the experimental groups which provide a new understanding on ozone inhalation exposure on inflammatory systems.